Legal Protection for Wives due The Annulment of A Marriage: A Maqasid Al-Shari'ah Perspective A Study of Religious Court Rulings in Indonesian - Pulungan, Muhammad Alfi Syahrin; Lubis, Syaddan Dintara (KALOSARA: Family Law Review, 2026)
The study examines the legal protection afforded to good-faith wives in marriage annulment cases and explores the integration of maqāṣid al-sharīʿah principles into judicial reasoning. Although the Indonesian Marriage Law and the Compilation of Islamic Law regulate the grounds for annulment, previous studies have not addressed the normative gap concerning the post-annulment rights of wives. This gap namely, the absence of substantive protection for wives who suffer harm due to identity fraud or deception constitutes the central focus of the research. Using a normative juridical method supported by statutory, doctrinal, and case law analysis, the study finds that judicial practice remains predominantly formalistic. Marriage annulment is treated as nullifying all legal consequences from the outset, which ultimately disadvantages wives acting in good faith. An analysis based on maqāṣid al-sharīʿah, particularly the principle of ḥifẓ al-nafs, indicates that annulment decisions should account for humanitarian considerations, prevention of harm, and the preservation of women's dignity. This research contributes to the development of Islamic family law discourse by proposing a more progressive interpretive framework that incorporates maqāṣid al-sharīʿah into judicial decision-making. The findings carry practical implications for religious courts in Indonesia, emphasizing the need to recognize and protect the rights of wives more comprehensively in annulment cases, as well as encouraging the development of regulations that respond more effectively to women's vulnerability.   Keywords: Hifz Al-Nafs; Maqasid Al-Shariah; Marriage Annulment.